Doing more digital humanities : open approaches to creation, growth, and development - Crompton, Constance (Constance Louise Kathleen); Lane, Richard J., 1966-; Siemens, Raymond George, 1966- (Routledge/Taylor & Francis Group, 2020)
"As digital media, tools, and techniques continue to impact and advance the humanities, Doing More Digital Humanities provides practical information on how to do digital humanities work. This book offers: A comprehensive, practical guide to the digital humanities ; Accessible introductions, which in turn provide the grounding for the more advanced chapters within the book ; An overview of core competencies, to help research teams, administrators, and allied groups, make informed decisions about suitable collaborators, skills development, and workflow ; Guidance for individuals, collaborative teams, and academic managers who support digital humanities researchers ; Contextualized case studies, including examples of projects, tools, centres, labs, and research clusters ; Resources for starting digital humanities projects, including links to further readings, training materials and exercises, and resources beyond ; Additional augmented content that complements the guidance and case studies in Doing Digital Humanities"-- Provided by publisher
Keywords: Digital humanities.; Humanities -- Research -- Methodology.; Humanities -- Study and teaching (Higher); Internet in education.; Sciences humaines numériques.; Internet en éducation.; digital humanities.; LANGUAGE ARTS & DISCIPLINES -- Library & Information Science.; Digital humanities; Humanities -- Research -- Methodology; Internet in education